Innovations of Governance in Balinese Joged Bumbung Dance in the era of globalization - I Gede Arya Sugiartha (Institut Seni Indonesia Denpasar, 2018)
This paper aims to analyze the develpmental dynamics concerning the governance of Balinese Joged Bumbung performances in the era of globalization. Developments being analyzed involve innovations in governance of performance standards. The methodologies utilized in conducting this research include observations, interviews, and literature studies. Post-modern aesthetic theory is utilized for analysis of phenomena such as, receptivity aesthetics and aesthetics in relation to social facts and arts of the community (Mukarovsky, 1970). Organizational innovation is a manifestation of changes in aesthetic functions by the role of supporting art, Baliâ€™s Joged Bumbung which exists as social dance. In recent developments many manifestations of this art form have been ridiculed as joged ngeborÂ (meaning â€œdrillâ€ with pornographic connotations), also is much appreciated as innovative joged (joged care jani) due to a change in governance of performance standards. This happens because of the interplay of extraneous factors (peopleâ€™s taste and the influence of television entertainment arts), as well as intrinsic forces (creative power and pragmatic attitudes of performers). The taste of the people who want dancers to move in this ngebor mannerÂ is understood to be pragmatic by the performers whose affirmation of these movement modalities only for the sake of monetary interest (economic goals). Even though there are also Joged Bumbung Bali innovations; which are creative in organizing performances without being eroded to appear as pornographic and are still in demand by the community. The offer of a model of grooming performance, which prioritizes creativity in the development of accompaniment music and dance movements, has been an innovative Baliâ€™s Joged Bumbung as an offer to fight the tendancy to be erotic.